Mononuclear Copper Complexes with Tridentate Tris(N-heterocyclic carbene): Synthesis and Catalysis of Alkyne-Azide Cycloaddition - Seo, Changhyeon; Cheong, Yeon Joo; Yoon, Woojin; Kim, Jaegyeom; Shin, Jinho; Yun, Hoseop; Kim, Seung Joo; Jang, Hye Young (Organometallics, 2021)
Mononuclear copper complexes modified with tridentate tris(N-heterocyclic carbene) (triscarbene) ligands are synthesized. The structures of the copper-triscarbene complexes are characterized using X-ray crystallography, X-ray absorption near edge structure (XANES), and extended X-ray absorption fine structure (EXAFS) analyses. These copper-triscarbene complexes are utilized for the cycloaddition of alkynes and azides, and kinetic study results are presented.
Keywords: Extended x-ray absorption fine structure analysis; Kinetic study; Mononuclear copper complexes; N-heterocyclic carbenes; X-ray absorption near-edge structure